1990
DOI: 10.1152/ajpgi.1990.258.4.g576
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal luminal polyamines: cellular accumulation and enterohepatic circulation

Abstract: The concentration of polyamines contained in the lumen of the gut was quantified. The duodenum and jejunum of the rat contained 2-3 mM putrescine and 1-2 mM cadaverine, whereas in the ileum and colon the concentration of these polyamines was significantly less. In addition, the concentrations of spermine and spermidine in the intestinal lumen were low to undetectable. Putrescine in the lumen of the gut was over 90% free with only 10% or less bound to protein. The activity of the enzymes responsible for the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 0 publications
4
53
0
1
Order By: Relevance
“…The polyamine levels observed in the pigs' intestine are closer in range than those previously reported in rats [16,21] and in healthy humans [3]. In rats, the highest lumenal concentrations of polyamines were observed in the jejunum, indicating a polyamine supply in the upper part of the intestine and subsequent absorption along the intestine from the jejunum to the ileum [21]. This pattern was not observed in the present study.…”
Section: Lumenal Polyaminessupporting
confidence: 70%
“…The polyamine levels observed in the pigs' intestine are closer in range than those previously reported in rats [16,21] and in healthy humans [3]. In rats, the highest lumenal concentrations of polyamines were observed in the jejunum, indicating a polyamine supply in the upper part of the intestine and subsequent absorption along the intestine from the jejunum to the ileum [21]. This pattern was not observed in the present study.…”
Section: Lumenal Polyaminessupporting
confidence: 70%
“…Increasing evidence indicates that the natural polyamines spermidine and spermine and their precursor, putrescine, are the central convergence point for the multiple signaling pathways driving different epithelial cell functions. We (8 -10) and others (11,12) have shown that normal intestinal epithelial growth depends on the supply of polyamines to the dividing cells in the crypts, and that differentiated epithelial cells of the mucosal surface are also exposed to the high concentrations of polyamines in the luminal contents of the intestine (13). Recently, polyamines have been implicated in the control of the apoptotic response in intestinal epithelial cells (14 -16).…”
mentioning
confidence: 99%
“…Polyamines may also increase the virulence potential of UPEC by modifying biofilm formation, affecting the conductivity of outer membrane porins, and/or altering the expression of secreted toxins and iron-chelating agents (51,56). Notably, polyamines are abundant within the intestinal tract (13,46) and can also be found in substantial quantities within vaginal secretions (9,34), where they may interact with and phenotypically modulate UPEC prior to entry into the urinary tract. UPEC may also encounter high levels of polyamines within the urinary tract, where urine polyamine concentrations can be elevated as a consequence of pregnancy or UTI (1,55).…”
Section: Discussionmentioning
confidence: 99%